Cardio‐Renal Biomarker Soluble Urokinase‐Type Plasminogen Activator Receptor Is Associated With Cardiovascular Death and Myocardial Infarction in Patients With Coronary Artery Disease Independent of Troponin, C‐Reactive Protein, and Renal Function. Issue 8 (21st April 2020) - Nikorowitsch, Julius; Borchardt, Tim; Appelbaum, Sebastian; Ojeda, Francisco; Lackner, Karl J.; Schnabel, Renate B.; Blankenberg, Stefan; Zeller, Tanja; Karakas, Mahir
Abstract : Background: Risk stratification among patients with coronary artery disease (CAD) is of considerable interest due to the potential to guide secondary preventive therapies. Thus, we evaluated the predictive value of soluble urokinase‐type plasminogen activator receptor (suPAR) levels for cardiovascular mortality and nonfatal myocardial infarction in patients with CAD. Methods and Results: Plasma levels of suPAR were measured in a cohort of 1703 patients with documented CAD as evidenced by coronary angiography—including 626 patients with acute coronary syndrome and 1077 patients with stable angina pectoris. Cardiovascular death and/or nonfatal myocardial infarction were defined as main outcome measures. During a median follow‐up of 3.5 years, suPAR levels reliably predicted cardiovascular death or myocardial infarction in CAD, evidenced by survival curves stratified for tertiles of suPAR levels. In Cox regression analyses, the hazard ratio for the prediction of cardiovascular death and/or myocardial infarction was 2.19 ( P <0.001) in the overall cohort and 2.56 in the acute coronary syndrome cohort ( P <0.001). Even after adjustment for common cardiovascular risk factors, renal function and the biomarkers C‐reactive protein, N‐terminal pro‐B‐type natriuretic peptide and high‐sensitivity troponin I suPAR still enabled a reliable prediction of cardiovascular death or myocardial infarction with a hazard ratio of 1.61 ( P =0.022) in the overall cohort and 2.22 ( P =0.005) in the acute coronary syndrome cohort. Conclusions: SuPAR has a strong and independent prognostic value in secondary prevention settings, and thereby might represent a valuable biomarker for risk estimation in CAD.